2017
DOI: 10.2298/vsp160127297v
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic cephalometry analysis of head posture and craniofacial morphology in oral breathing children

Abstract: Background/Aim. Nasal breathing plays an important role in overall physical growth and mental development, as well as in the growth of the craniofacial complex. Oral breathing over a long period of time, can cause changes in position of the head relative to the cervical spine and jaw relationship. It can cause an open bite and the narrowness of the maxillary arch due to increased pressure of strained face. The aim of this study was to analyze the position of the head and craniofacial morphology in oral breathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…By constantly keeping the mouth ajar, RBs cause hypofunction of the orofacial muscles, which leads to a deterioration of certain phonemes such as: t, d, s, z, r [1,8].…”
Section: Pathologies Associated With Mouth Breathingmentioning
confidence: 99%
See 2 more Smart Citations
“…By constantly keeping the mouth ajar, RBs cause hypofunction of the orofacial muscles, which leads to a deterioration of certain phonemes such as: t, d, s, z, r [1,8].…”
Section: Pathologies Associated With Mouth Breathingmentioning
confidence: 99%
“…Nasal breathing plays a substantial role in the growth and development of the craniofacial complex [1]. The main function of the nose is to moisten, warm and purify inhaled air from dust and bacteria before it is carried into the lungs [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of children with long-face growth patterns also remains to be a challenging clinical problem. In recent years, the number of children with nasopharyngeal airway obstructive diseases has been increasing, and the resulting compensatory mouth breathing is the main cause of dental and maxillofacial deformities in these children 1…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the number of children with nasopharyngeal airway obstructive diseases has been increasing, and the resulting compensatory mouth breathing is the main cause of dental and maxillofacial deformities in these children. 1 We investigated the prevalence of deciduous dentition malocclusion among children aged between 3 and 5 years in Shanghai and analysed the correlation between malocclusion and oral habits, dietary structure and upper respiratory diseases. 2 Researchers have found that chronic rhinitis and adenotonsillar hypertrophy are highly correlated with mouth breathing, 3 accompanied by a higher prevalence of hyperdivergent malocclusion.…”
Section: Introductionmentioning
confidence: 99%